Islet amyloid polypeptide exerts a novel autocrine action in β‐cell signaling and proliferation. Issue 7 (25th March 2015) - Visa, Montse; Alcarraz‐Vizán, Gema; Montane, Joel; Cadavez, Lisa; Castaño, Carlos; Villanueva‐Peñacarrillo, María Luisa; Servitja, Joan‐Marc; Novials, Anna
ABSTRACT: The toxic effects of human islet amyloid polypeptide (IAPP) on pancreatic islets have been widely studied. However, much less attention has been paid to the physiologic actions of IAPP on pancreatic β cells, which secrete this peptide together with insulin upon glucose stimulation. Here, we aimed to explore the signaling pathways and mitogenic actions of IAPP on β cells. We show that IAPP activated Erk1/2 and v‐akt murine thymoma viral oncogene homolog 1 (Akt) at the picomolar range (10‐100 pM) in mouse pancreatic islets and MIN6 β cells cultured at low glucose concentrations. In contrast, IAPP decreased the induction of these pathways by high glucose levels. Consistently, IAPP induced a 1.7‐fold increase of β‐cell proliferation at low‐glucose conditions, whereas it reduced β‐cell proliferation at high glucose levels. Strikingly, the specific antagonist of the IAPP receptor AC187 (100 nM) decreased the activation of Erk1/2 and Akt and reduced β‐cell proliferation by 24% in glucose‐stimulated β cells, uncovering a key role of endogenously released IAPP in β‐cell responses to glucose. We conclude that exogenously added IAPP exerts a dual effect on β‐cell mitogenic signaling and proliferation, depending on the glucose concentration. Importantly, secreted IAPP contributes to the signaling and mitogenic response of β cells to glucose through an autocrine mechanism.— Visa, M., Alcarraz‐Vizán, G., Montane, J., Cadavez, L., Castaño, C., Villanueva‐Peñacarrillo, M. L., Servitja, J.‐M., Novials, A. Islet amyloid polypeptide exerts a novel autocrine action in β‐cell signaling and proliferation. FASEB J . 29, 2970‐2979 (2015). www.fasebj.org